2021
DOI: 10.1111/andr.13017
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of sperm membrane integrity and DNA fragmentation by flow cytometry: A novel and rapid tool for sperm analysis

Abstract: Background: Sperm DNA integrity has become one of the most discussed and promising biomarkers for the assessment of male fertility. However, an easy-to-apply method capable of estimating DNA fragmentation in the live fraction of spermatozoa has remained elusive, preventing this parameter from being fully applied in clinical settings.Objectives: To validate a novel co-staining for the analysis of DNA fragmentation in membrane-intact spermatozoa.Materials and methods: Normozoospermic semen samples were used to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The relation of DFI to other sperm parameters or factors such as sperm membrane integrity remains controversial. Several studies found negative correlations with conventional semen parameters, while others could not reproduce these associations [44][45][46]. In this study, we could demonstrate several significant correlations with other sperm parameters.…”
Section: Cp/cpps and Sperm Dna Fragmentationsupporting
confidence: 55%
“…The relation of DFI to other sperm parameters or factors such as sperm membrane integrity remains controversial. Several studies found negative correlations with conventional semen parameters, while others could not reproduce these associations [44][45][46]. In this study, we could demonstrate several significant correlations with other sperm parameters.…”
Section: Cp/cpps and Sperm Dna Fragmentationsupporting
confidence: 55%
“…[37][38][39] Further, methods of preparation of spermatozoa for the assessment of DNA damage and the selection of different detection techniques can influence DNA integrity. 40 Hence, these factors, which are often neglected, need to be addressed while deciding the clinical value of sperm DNA integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is important to note that suboptimal laboratory conditions, such as handling, prolonged incubation, and centrifugation, can influence sperm DNA integrity 37–39 . Further, methods of preparation of spermatozoa for the assessment of DNA damage and the selection of different detection techniques can influence DNA integrity 40 . Hence, these factors, which are often neglected, need to be addressed while deciding the clinical value of sperm DNA integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The sperm chromatin structure assay, used to detect the DNA fragmentation index (DFI), is a routine test to estimate sperm DNA damage. Recently, a simultaneous detection of sperm membrane integrity and DNA fragmentation assay was tested using flow cytometry and co-staining, consisting of acridine orange (AO) and LIVE/DEAD™ fixable blue dead cell stain [ 75 ], to estimate sperm quality prior to selection for ART. In the case of high DNA fragmentation, testicular sperm can be selected for ICSI.…”
Section: Diagnosing Male Infertility In Pcd Patientsmentioning
confidence: 99%